The Association Between Serum Uric Acid Levels and the 10‐Year Prospective Risk of Dyslipidemia: A Cohort Study From Healthy Heart Project (YHHP) - Hamidreza Mohammadi; Seyed Reza Mirjalili; Pedro Manuel Marques‐Vidal; Marzieh Azimizadeh; Seyede Mahdiah Nemayandah; Mohammadtaghi Sarebanhassanabadi; Sedighe Sadeghi (Health Science Reports)
ABSTRACT Background and Aims Dyslipidemia is a major risk factor for cardiovascular disease (CVD) and is increasingly prevalent globally, particularly in developing countries undergoing lifestyle transitions. Serum uric acid (SUA) has been implicated in various metabolic disorders, including dyslipidemia. This study aimed to evaluate the association between high SUA and the 10‐year prospective risk of dyslipidemia. Methods This cohort study uses data from the Yazd Healthy Heart Project (YHHP). Participants were followed for 10 years, during which the association between dyslipidemia incidence and SUA levels was assessed using multivariate Cox proportional hazard models. Results Among 693 participants analyzed, higher SUA quartiles were associated with older age, male gender, and adverse anthropometric and metabolic profiles. Elevated SUA levels correlated positively with triglycerides (r = 0.21, p < 0.001), total (r = 0.13, p < 0.001) and low‐density lipoprotein cholesterol (r = 0.12, p = 0.001) levels, but not with high‐density lipoprotein cholesterol (r = 0.07, p > 0.05). After adjusting for age, lifestyle factors, and metabolic parameters, the incidence of dyslipidemia increased across SUA quartiles in males, with adjusted hazard ratios of 1.33 (95% CI: 0.90–1.97), 1.66 (95% CI: 1.10–2.54), and 1.79 (95% CI: 1.17–2.72) for the second, third, and fourth quartiles of SUA, respectively (p for trend 0.001), but not in females: 1.11 (95% CI: 0.59–2.06), 0.95 (95% CI: 0.55–1.64), and 1.14 (95% CI: 0.60–2.16), respectively, p for trend 0.86. Conclusion Elevated SUA levels independently associated with the development of dyslipidemia over a decade in an Iranian population. The findings underscore the potential utility of SUA as a biomarker for assessing dyslipidemia risk, particularly in men. Further research should explore mechanistic pathways linking SUA to dyslipidemia and evaluate interventions targeting SUA reduction to mitigate dyslipidemia risk.